Septins Focus Cellular Growth for Host Infection by Pathogenic Fungi - Momany, Michelle; Talbot, Nicholas J. (Frontiers in Cell and Developmental Biology, 2017)
One of the key challenges faced by microbial pathogens is invasion of host tissue. Fungal pathogens adopt a number of distinct strategies to overcome host cell defenses, including the development of specialized infection structures, the secretion of proteins that manipulate host responses or cellular organization, and the ability to facilitate their own uptake by phagocytic mechanisms. Key to many of these adaptations is the considerable morphogenetic plasticity displayed by pathogenic species. Fungal pathogens can, for example, shift their growth habit between non-polarized spores, or yeast-like cells, and highly polarized hyphal filaments. These polarized filaments can then elaborate differentiated cells, specialized to breach host barriers. Septins play fundamental roles in the ability of diverse fungi to undergo shape changes and organize the F-actin cytoskeleton to facilitate invasive growth. As a consequence, septins are increasingly implicated in fungal pathogenesis, with many septin mutants displaying impairment in their ability to cause diseases of both plants and animals. In this mini-review, we show that a common feature of septin mutants is the emergence of extra polar outgrowths during morphological transitions, such as emergence of germ tubes from conidia or branches from hyphae. We propose that because septins detect and stabilize membrane curvature, they prevent extra polar outgrowths and thereby focus fungal invasive force, allowing substrate invasion.